Implementasi Teknologi AWS Cloud Dalam Pengembangan Aplikasi Ujian Online Berbasis Website Menggunakan Framework Codeigniter (Studi Kasus: SMAN 1 Jombang dan MAN 9 Jombang) - Ryan Bayu Permadi; Tibyani Tibyani; Issa Arwani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
The online test is a test that utilizes computers as a medium that replaces paper in the implementation of the exam. SMAN 1 Jombang and MAN 9 Jombang still uses conventional based exams where the exams still use paper media in their implementation, so teachers still have difficulty in correcting the results of the exams which makes the teacher correcting the exam takes quite a long time. In this online test application utilizing the services of Amazon Web Service as a server and storage. By utilizing the Ec2 and AWS Rds Database it is hoped that the online exam application can be accessed online and can be accessed by many people. With the construction of this system makes it easy for students to do the exam without having to face-to-face and makes it easier for teachers to hold examinations at school. The method used in developing online exam applications is the waterfall method where in the first stage, namely the study of literature to making conclusions. The tests used in this research are the Blackbox Testing method and the System Usability Scale. The results showed 32 respondents from SMAN 1 Jombang got SUS 71.09 results which were included in the acceptable or good category and at MAN 9 Jombang got SUS 72.29 results included in the acceptable or good category